Effect of Vessel Tortuosity on Stress Concentration at the Distal Stent–Vessel Interface: Possible Link With New Entry Formation Through Biomechanical Simulation - Wei, Ting Tan; Yih, Miin Liew; Mohd Jamil Mohamed, Mokhtarudin; Pirola, Selene; Wan Naimah, Wan Ab Naim; Shahrul Amry, Hashim; Xiao, Yun Xu; Einly, Lim (The American Society of Mechanical Engineers, 2021)
A computational approach is used to investigate potential risk factors for distal stent graft-induced new entry (dSINE) in aortic dissection (AD) patients. Patient-specific simulations were performed based on computed tomography images acquired from six AD patients (three dSINE and three non-dSINE) to analyze the correlation between anatomical characteristics and stress/strain distributions. Sensitivity analysis was carried out using idealized models to independently assess the effect of stent graft length, stent tortuosity and wedge apposition angle at the landing zone on key biomechanical variables. Mismatch of biomechanical properties between the stented and nonstented regions led to high stress at the distal stent graft–vessel interface in all patients, as well as shear strain in the neighboring region, which coincides with the location of tear formation. Stress was observed to increase with the increase of stent tortuosity (from 263 kPa at a tortuosity angle of 50 deg to 313 kPa at 30 deg). It was further amplified by stent graft landing at the inflection point of a curve. Malapposition of the stent graft led to an asymmetrical segment within the aorta, therefore changing the location and magnitude of the maximum von Mises stress substantially (up to +25.9% with a +25 deg change in the distal wedge apposition angle). In conclusion, stent tortuosity and wedge apposition angle serve as important risk predictors for dSINE formation in AD patients.